Digital Technologies for School Collaboration - Gouseti, Anastasia; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Drawing on a wealth of theoretical and empirical work, this book provides a comparative, comprehensive, and critical perspective on the use of digital technologies for collaboration between schools.
Keywords: Science; Science; Science, general